Printed log-periodic trapezoidal dipole array antenna with a balun-feed for ultra-wideband applications - Zengin, Fatma; Akkaya, Eren; Gunes, Filiz; Ecevit, Fevzi Necati (WILEY, 2018)
The authors present design of a printed log-periodic trapezoidal dipole array (PLPTDA) antenna with a balun-feed operating throughout the 2-18GHz frequency range. For this purpose, the antenna is designed and simulated in the CST Microwave Studio environment. Thus, better directivity along the operation bandwidth is achieved via the iterative simulations with a 33.33% reduction in the dipole length at the lowest frequency 2GHz as compared with the counterpart standard log-periodic antennas. Furthermore, they fabricated the PLPTDA antenna with and without the balun-feed. Thus, influence of the balun on the performance is investigated and the average gain of the PLPTDA antenna with the balun-feed is measured as 8.16dBi provided voltage standing wave ratio (VSWR) < 2, which agrees with the simulation results. Furthermore, these measured gain/directivity results are compared with the counterpart antennas' measured performances in the literature considering their operation bandwidths and sizes. It can be concluded that their proposed PLPTDA antenna will prove to be useful in both wideband civilian and military applications in the S, C, X, and Ku bands within the 1:9 ultra-wideband bandwidth which is the largest achieved in this class antenna technology in the literature up to now.
Keywords: microstrip antenna arrays; log periodic antennas; dipole antenna arrays; baluns; antenna feeds; iterative methods; printed log-periodic trapezoidal dipole array antenna; balun-feed; ultra-wideband applications; microstrip PLPTDA; CST Microwave Studio environment; iterative simulations; LPDA ANTENNA; Engineering; Telecommunications